The comparison of public and private primary schools children physical fitness - ÇAMLIGÜNEY, ASİYE FİLİZ; SOYKAN, AYTEKİN; RAMAZANOĞLU, NUSRET; YILMAZ, SEMİH (ELSEVIER SCIENCE BV, 2012)
To study the effect of differences between public and private primary schools sharing a common curriculum. Between the ages of 7 and 11, educated in public and private primary schools were included in this study. Girls and boys participating in physical education classes were evaluated on right-left hand grip and leg strength using a dynamometer; on flexibility, using sit-and-reach flexibility test; on balance, using flamingo balance test and on coordination, hand-eye coordination test. The results of the effect of physical education on physical fitness of children displayed statistically significant differences only in leg strength.
Keywords: physical education; physical fitness; primary school; children; HAND-EYE COORDINATION; MOTOR-SKILLS; CUP STACKING